Public Relations Strategy of the West Java Province Cooperative and Small Business Service in Increasing the Active Role of Secondary Cooperatives in West Java - Iing Saefudin; Teuku Yuliansyah; Risma A. Nabilah; Anisa Rusanti (International Journal of Science and Society, 2023)
Effective Public Relations Communication between the West Java Province Cooperative and MSME Service can help people increase awareness about the Secondary Cooperative program and how they can use it for their benefit. To achieve this goal, an appropriate communication strategy is needed. This research then aims to see how the Public Relations strategy of the Cooperatives and Small Business Office of West Java Province is increasing the active role of Secondary Cooperatives in West Java. This research will be carried out using a descriptive qualitative approach. Research data was obtained through various methods such as literature studies and interviews. The results of this research then found that the public relations strategy at the Department of Cooperatives and Small Businesses of West Java Province could be carried out through 4 phases. Aspects of the formative research phase help ensure that communication campaigns or programs are designed according to the needs and preferences of the audience, and are more effective in achieving the stated communication goals. Aspects of the strategy phase are carried out through a series of steps or methods to convey messages and information to the audience, namely the fostered secondary cooperative. Aspects of the tactical phase are carried out by documenting on social media and collaborating. Finally, evaluation research aspects are carried out periodically through evaluation meetings, both external and internal.